Review on Cassia alata Bioactive Compounds: In silico, in vitro, and in vivo Studies - Colin MN; Claudiana NSE; Kaffah AU; Hasanah AN; Megantara S (Dove Medical Press, 2024)
Michelle Natasha Colin, Nur Shelly Ester Claudiana, Annisa Utami Kaffah, Aliya Nur Hasanah, Sandra Megantara Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Aliya Nur Hasanah; Sandra Megantara, Department of Pharmaceutical Analysis and Medicinal Chemistry, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Sumedang, 45363, Indonesia, Email aliya.n.hasanah@unpad.ac.id; s.megantara@unpad.ac.idAbstract: Cassia alata Linn is a popular herbal remedy in many countries, and its activities have been studied through many studies, starting from in silico, in vitro, and in vivo. This narrative review will focus more on secondary metabolites that are responsible for certain pharmacological activities that have undergone in vivo, in vitro, and in silico testing to determine the underlying mechanism. Twenty pharmacological activities have been identified, with the flavonoid group (emodin, kaempferol, quercetin) as the most prevalent secondary metabolite found in Cassia alata. There have been numerous studies looking at the role of flavonoids about specific diseases, and flavonoid testing is quite thorough because it covers three different study types. However, there has not been significant progress accomplished in terms of the evaluation of the dosage form so that test results for promising activities like antidiabetic, antifungal, and antiviral can be carried out into further research. Additionally, several disorders lack comprehensive investigation, particularly in silico studies, therefore further study is required to fill any gaps in the knowledge.Keywords: Cassia alata, pharmacological activity, chemical compound, in silico, in vitro, in vivo